KEMAMPUAN LEMPARAN KE DALAM PADA SEPAK BOLA - Sukirno (Universitas Negeri Semarang, 2014)
The purpose of this study was to determine whether there is a relationship togok flexibility and muscle power arm with a throw into the game of football, this research is expected to help teachers and sports coaches, especially at football, to be able to optimize the results of his training, especially on techniques throw into. The method used in this study is the correlation method. The study population was a class VIII student of the Junior High School Kayuagung total of 120 students, the study sample as many as 60 students. The technique of collecting data through physical tests. While the techniques of data analysis using correlation test using SPSS. The results obtained by the analysis of the data showed a positive relationship between flexibility togok to throw into the game of football, with the result "r" of 0.70. That is togok flexibility contributes to toss into by 70 %. While the muscle power arm with a throw-in "r" of 0.79. That is the power arm muscles contributes 79 % to throw into . The results of the processing and analysis of data shows that there is a positive relationship . Taken together togok flexibility and muscle power arm with a throw-in on the game of football "R" 0.90. That is togok flexibility and muscle power arm together memebrikan contribution of 90 % to throw into the game of football. based on these results we can conclude that there was a significant relationship togok flexibility and muscle power arm to throw into the men's soccer game eighth grade students of SMP Negeri 1 Kayuagung